Dissemination of Digital Marketing and Branding Products at Mia Coffee Managers at Ma'had Ihya' Al Ahmadi, Kampung Sungai Kelambu, Selangor, Malaysia - Kurniawati Meylianingrum; Zahwa Angelica; Yayuk Sri Rahayu (As-sunnah: Jurnal Pengabdian Masyarakat, 2024)
MIA Coffee is a business venture owned by Maahad Ihya Al Ahmadi in Kampung Sungai, Kelambu, Selangor, Malaysia. The management of MIA Coffee comes from staff and teachers at the same school. However, this business wants to be developed so that people outside the Islamic boarding school can enjoy it. Therefore, it is necessary to have skills in digital marketing and branding of Islamic products. The method used in this service uses service learning activities, where students of the International KKM UIN Maulana Malik Ibrahim Malang provide training related to courses taught by lecturers who are experts related to this. The result of this service is the understanding of the administrators and the opening of MIA Coffee for the community around the Islamic boarding school. The limitation of this community service is that it has not been included in creating social media and marketplaces to implement the results of digital marketing and Islamic product branding dissemination.